Karakteristik Kefir Susu Sapi Dengan Penambahan Ekstrak Bunga Telang (Clitoria ternatea) - Amelia Friska Pertiwi; Epi Taufik; Irma Isnafia Arief (Institut Pertanian Bogor, 2023)
Kefir is made from a kefir seed starter consisting of L kefiri, genus Leuconostoc, Lactococcus, and Acetobacter that grow side by side. The addition of butterfly pea flowers extract to kefir can improve functional properties and sensory. The aim of this study was to investigate the physical characteristic, chemical characteristics, microorganisms, antioxidant activity, and organoleptic properties of cow’s milk kefir with the addition of butterfly pea flowers during storage at refrigerator temperature (1‒4°C). The research analysis used a completely randomized design with a 3x3 factorial pattern with three repetitions. The first factor was the addition of butterfly pea flowers (0%, 3%, and 6%), and the second factor was storage time (0, 3, and 6 days). The physical, chemical, antioxidant activity, and microorganism characteristics were tested using two-factor ANOVA and further tested by the Duncan test. Data on organoleptic properties were analyzed by the nonparametric Kruskal-Wallis and then verified using the Mann-Whitney test. The results showed that during storage the kefir increased the pH value and TAT value and decreased the viscosity and fat content. The inhibition of DPPH and the antioxidant capacity of the addition of butterfly pea flowers extract increased and decreased with the length of storage. Lactic acid bacteria (LAB) and the yeast did not change. Sensory hedonic test panelists prefer the color and aroma of kefir with the addition of telang flower extract. Sensory test of hedonic quality with the best characteristics, namely the addition of 6% butterfly pea flowers extract. Keywords: butterfly pea extract, kefir, storage organoleptic